2008
DOI: 10.1242/jeb.013953
|View full text |Cite
|
Sign up to set email alerts
|

Identification, molecular structure and expression of two cloned serotonin receptors from the pond snail, Helisoma trivolvis

Abstract: SUMMARYHelisoma trivolvis has served as a model system to study the functions of serotonin (5-HT) from cellular, developmental, physiological and behavioural perspectives. To further explore the serotonin system at the molecular level, and to provide experimental knockout tools for future studies, in this study we identified serotonin receptor genes from the H. trivolvis genome, and characterized the molecular structure and expression profile of the serotonin receptor gene products. Degenerate oligonucleotide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 53 publications
2
26
0
Order By: Relevance
“…receptors, 5-HT 1Hel and 5-HT 7Hel , and it has been proposed that one of these is involved in prolongation of the response (Mapara et al, 2008). The results of the present study suggest that L. stagnalis also has a serotonin receptor that mediates the prolonged response.…”
Section: Characterization Of Pedal and Apical Plate Ciliasupporting
confidence: 54%
See 1 more Smart Citation
“…receptors, 5-HT 1Hel and 5-HT 7Hel , and it has been proposed that one of these is involved in prolongation of the response (Mapara et al, 2008). The results of the present study suggest that L. stagnalis also has a serotonin receptor that mediates the prolonged response.…”
Section: Characterization Of Pedal and Apical Plate Ciliasupporting
confidence: 54%
“…The results of the present study suggest that L. stagnalis also has a serotonin receptor that mediates the prolonged response. A potential candidate would be the 5-HT 1Lym serotonin receptor, which is a closely related homolog of 5-HT 1Hel (Sugamori et al, 1993;Mapara et al, 2008). It will be interesting to determine whether this receptor is expressed in ciliary tissues of L. stagnalis embryos and functions to produce sustained responses.…”
Section: Characterization Of Pedal and Apical Plate Ciliamentioning
confidence: 99%
“…These receptors, named 5-HT 1Hel and 5-HT 7Hel , respectively, are both expressed in embryonic ciliary cells, as well as in many neurons of the adult central nervous system (Mapara et al, 2008;Doran et al, 2004). A preliminary study of these suggested that 5-HT 1Hel receptors probably mediate a transient large-amplitude cilioexcitatory response to serotonin (Gallin et al, 2006).…”
Section: Embryonic Rotational Behaviour and The Underlying Physiologimentioning
confidence: 99%
“…Mianserin acts on the 5-HT-type II (5HT 2 ) receptor; however, whether this receptor is present in H. trivolvis embryos is unknown as only the 5-HT-type I H. trivolvis (5-HT 1Hel ) and 5-HT-type VII H. trivolvis (5-HT 7Hel ) receptors have been identified (Mitchell et al, 1990;Csaba et al, 2003;Mapara et al, 2008). It is difficult to conclude from the actions of mianserin that the 5-HT 2 receptor is present because of its poor specificity and the unreliability of transferring pharmacological profiles of vertebrate receptors to their invertebrate counterparts (Goldberg et al, 1994;HaySchmidt, 2000;Mapara et al, 2008).…”
Section: Energy Regulation Through a 5-ht Pathwaymentioning
confidence: 99%
“…It is difficult to conclude from the actions of mianserin that the 5-HT 2 receptor is present because of its poor specificity and the unreliability of transferring pharmacological profiles of vertebrate receptors to their invertebrate counterparts (Goldberg et al, 1994;HaySchmidt, 2000;Mapara et al, 2008). It appears that mianserin is an effective antagonist on whichever receptor is linked to acute 5-HT-stimulated rotation.…”
Section: Energy Regulation Through a 5-ht Pathwaymentioning
confidence: 99%